Giant shape memory and domain memory effects in antiferroelectric single crystals. Issue 8 (15th May 2019) - Zhuo, Fangping; Damjanovic, Dragan; Li, Qiang; Zhou, Yaming; Ji, Yongjie; Yan, Qingfeng; Zhang, Yiling; Zhou, Yun; Chu, Xiangcheng
Abstract : Giant shape memory and domain memory effects may promote the development of new antiferroelectric or ferroelectric devices. Abstract : We report irreversible and reversible antiferroelectric–ferroelectric phase transitions, shape memory and domain memory effects in (Pb, La)(Zr, Sn, Ti)O3 antiferroelectric tetragonal single crystals. We find that electric-field-induced antiferroelectric to ferroelectric phase transition is an irreversible process at temperatures below the depolarization temperature (∼50 °C), and achieves a giant shape memory strain value of 0.70% at room temperature. With the help of an in situ polarized light microscope, we discover a reversible phase transition between antiferroelectric and ferroelectric phases and a domain memory effect during electric field cycling above the depolarization temperature. In addition, single crystal X-ray diffraction results reveal that field-induced transformations between incommensurate antiferroelectric and commensurate ferroelectric modulations enable the emergence of shape and domain memory effects. A physical picture is proposed to explain these phase-transformation-mediated memory effects. Their discovery is expected to stimulate a systematic research upsurge of domain engineering and structure–property relationships in the quest for developing new antiferroelectric or ferroelectric devices.